Effect of canopy profile on solar thermal chimney performance. (May 2016) - Cottam, P.J.; Duffour, P.; Lindstrand, P.; Fromme, P.
Highlights: Efficient, steady state analytical simulation of STC power plant. Detailed collector model, taking into account varying heat transfer and fluid dynamics. Collector outlet height shown to have large impact on power output. Different collector canopy profiles studied, best configuration evaluated. Simpler to construct, segmented or stepped canopy profile proposed. Abstract: Solar thermal chimneys (STCs) are renewable energy power plants that require large-scale deployment to be economically competitive. This paper presents a steady-state analytical model developed to describe accurately the thermodynamics of the solar collector. The impact of different collector canopy designs on the performance is assessed. Results show that the height of the canopy has a significant effect on plant performance and that the canopy must be sufficiently high at the junction with the chimney to ensure maximum kinetic energy in the flow at the chimney inlet can be reached. A new collector profile with a partially sloped canopy is proposed. It was found to perform at similar levels of maximum power output to the best-performing existing canopy designs, and to be robust under varying environmental conditions. For ease of construction and reduction of associated costs this canopy can be built in stepped annular flat sections with only a minor loss in performance.